Factors related to water quality and thresholds for microcystin concentrations in subtropical Brazilian reservoirs. Issue 3 (3rd July 2018) - Cunha, Davi Gasparini Fernandes; Dodds, Walter Kennedy; Loiselle, Steven Arthur
ABSTRACT: Studies of the environmental factors that lead to cyanotoxic blooms in tropical/subtropical reservoirs are limited. While technological advances for water treatment and remediation techniques can mitigate the effects of cyanobacterial blooms, the identification of initial drivers and tipping points for minimizing cyanotoxin concentrations could be more cost effective. We studied factors related to microcystin (MC) concentrations and estimated thresholds to limit MC using a water quality dataset from 6 subtropical Brazilian reservoirs. Reservoirs varied by water chemistry and toxin concentrations (MC yearly means <0.1–17 µg/L). Phytoplankton community composition in most reservoirs was dominated by cyanobacteria, and both nitrogen-fixing and non-fixing genera were common. We found positive correlations ( p  < 0.05, Spearman's rank) between MC and nutrients (ρ = 0.48–0.74) and chlorophyll a (Chl- a, ρ = 0.65) and a negative correlation between MC and total nitrogen/total phosphorus (TN/TP, ρ = −0.49). While no association between MC and water temperature was observed, MC normalized to Chl- a values were positively related to higher temperatures and lower wind velocities, indicating warmer and more stable waters had a higher probability of toxic blooms. We found thresholds for MC ≥0.1 and ≥1 µg/L related to cyanobacterial cell counts of 20 060–136 165 cells/mL, respectively, and for turbidity (5–12 NTU) and TP (0.016–0.028 mg/L), respectively. We considered these MC concentrations (0.1 and 1 µg/L) to account for different levels of toxin production. The thresholds were different from those published for temperate ecosystems but not consistently lower or higher. TN/TP molar ratios favored toxin concentration when ≤121, suggesting that less phosphorus in relation to nitrogen is necessary to allow MC production in subtropical freshwaters. High phosphorus concentrations can increase concentration of cyanotoxins in subtropical reservoirs, and our data confirm that global warming could exacerbate problems associated with toxic algal blooms.